Differences in clinical results after LINAC-based single-dose radiosurgery versus fractionated stereotactic radiotherapy for patients with vestibular schwannomas - Combs, Stephanie; Welzel, Thomas; Schulz-Ertner, Daniela; Huber, Peter E.; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2010)
PURPOSE: To evaluate the outcomes of patients with vestibular schwannoma (VS) treated with fractionated stereotactic radiotherapy (FSRT) vs. those treated with stereotactic radiosurgery (SRS). - METHODS AND MATERIALS: This study is based on an analysis of 200 patients with 202 VSs treated with FSRT (n = 172) or SRS (n = 30). Patients with tumor progression and/or progression of clinical symptoms were selected for treatment. In 165 out of 202 VSs (82%), RT was performed as the primary treatment for VS, and for 37 VSs (18%), RT was conducted for tumor progression after neurosurgical intervention. For patients receiving FSRT, a median total dose of 57.6 Gy was prescribed, with a median fractionation of 5 x 1.8 Gy per week. For patients who underwent SRS, a median single dose of 13 Gy was prescribed to the 80% isodose. - RESULTS: FSRT and SRS were well tolerated. Median follow-up time was 75 months. Local control was not statistically different for both groups. The probability of maintaining the pretreatment hearing level after SRS with doses of < or =13 Gy was comparable to that of FSRT. The radiation dose for the SRS group (< or =13 Gy vs. >13 Gy) significantly influenced hearing preservation rates (p = 0.03). In the group of patients treated with SRS doses of < or =13 Gy, cranial nerve toxicity was comparable to that of the FSRT group. - CONCLUSIONS: FSRT and SRS are both safe and effective alternatives for the treatment of VS. Local control rates are comparable in both groups. SRS with doses of < or =13 Gy is a safe alternative to FSRT. While FSRT can be applied safely for the treatment of VSs of all sizes, SRS should be reserved for smaller lesions.
Available online 13 July 2009
Gesehen am 06.06.2023